Probiotic Intake and Inflammation in Patients With Chronic Kidney Disease: An Analysis of the CKD-REIN Cohort - Wagner, Sandra; Merkling, Thomas; Metzger, Marie; Koppe, Laetitia; Laville, Maurice; Boutron-Ruault, Marie-Christine; Frimat, Luc; Combe, Christian; Massy, Ziad A.; Stengel, Bénédicte; Fouque, Denis (Frontiers in Nutrition, 2022)
Background and Aims Little is known about the effects of probiotics on inflammation in the context of chronic kidney disease (CKD). We investigated the association between probiotic intake and inflammation in patients with moderate-to-advanced CKD. Methods We performed a cross-sectional study of 888 patients with stage 3–5 CKD and data on serum C-reactive protein (CRP) levels and a concomitant food frequency questionnaire. We estimated the odds ratios (ORs) [95% confidence interval (CI)] for various CRP thresholds (>3, >4, >5, >6, and >7 mg/L) associated with three intake categories (no yoghurt, ordinary yoghurt, and probiotics from yoghurts or dietary supplements) and two frequency categories (daily or less than daily). Results The 888 study participants (median age: 70; men: 65%) had a median estimated glomerular filtration rate of 28.6 mL/min/1.73 m2 and a median [interquartile range] CRP level of 3.0 [1.6, 7.0] mg/L. Fifty-seven percent consumed ordinary yoghurt and 30% consumed probiotic yoghurt. The median intake frequency for yoghurt and probiotics was 7 per week. Relative to participants not consuming yoghurt, the ORs [95% CI] for CRP > 6 or >7 mg/L were significantly lower for participants consuming ordinary yoghurt (0.58 [0.37, 0.93] and 0.57 [0.35, 0.91], respectively) and for participants consuming probiotics (0.54 [0.33, 0.9] and 0.48 [0.28, 0.81], respectively), independently of age, sex, body mass index, CKD stage, cardiovascular disease, and fibre, protein and total energy intakes. The ORs were not significantly lower for CRP thresholds >3, >4, and >5 mg/L and were not significantly greater in daily consumers than in occasional consumers. Conclusion We observed independent associations between the consumption of yoghurt or probiotics and lower levels of inflammation in patients with CKD. There was no evidence of a dose-effect relationship. Clinical Trial Registration [https://www.clinicaltrials.gov/ct2/show/NCT03381950], identifier [NCT03381950].